Effect of vitamin D levels on the hormonal and metabolic status in patients with metabolic syndrome and chronic kidney disease - O. A. Osipova; E. V. Gosteva; N. I. Zhernakova; O. N. Belousova; Yu. V. Tatarintseva; А. N. Khachaturov (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To assess the association of vitamin D deficiency with hormonal and metabolic disorders, including with insulin resistance and leptin levels, in patients with metabolic syndrome (MS) and chronic kidney disease (CKD).Material and methods. The study included 81 patients with MS and CKD aged 45-59 years (mean age, 51±4 years). Depending on vitamin D level, the patients were divided into two groups: group 1 (n=49) — patients with reduced level (23,2±5,1 ng/ml); group 2 (n=32) — patients with an adequate level (54,8±12,1 ng/ml). Statistical processing was carried out using STATISTICA 10.0 software.Results. In patients of the first group, the following parameters were higher than in the second one: waist circumference by 9,0% (p<0,05), waist-to-hip ratio by 8,2% (p<0,05), body mass index by 15,1% (p<0,05). The groups did not differ significantly in systolic and diastolic blood pressure levels. In the first group, the level of total cholesterol by 18,6% (p<0,01), low density lipoprotein cholesterol by 11,9% (p<0,05), triglycerides by 20,8% (p<0,01), Homeostasis Model Assessment Insulin Resistance (HOMA-IR) by 42,5% (p<0,001), leptin by 30,5% (p<0,01) were higher than in the second group. More severe left ventricular diastolic dysfunction in the first group than in the second one was determined as follows: lower left ventricular early to late filling (E/A) by 13,2% (p<0,05) and deceleration time of the early transmitral flow velocity by 13,1% (p<0,05).Conclusion. The results obtained indicate that patients with MS, CKD and vitamin D deficiency are more likely to have general obesity, more pronounced carbohydrate (HOMA-IR index) and fat (levels of total cholesterol, low-density lipoprotein cholesterol, triglycerides) metabolism disorders, as well as high serum levels of leptin compared with patients with adequate levels of this vitamin.